Efektivitas Model Project Based Learning Terhadap Sikap Kewarganegaraan Peserta Didik MI dalam Pembelajaran PPKn - Cahyati, Amalia Nur (Yayasan Zia Salsabila, 2022)
This study addresses the issue of inadequate internalization of civic values in Civic Education (Pendidikan Pancasila dan Kewarganegaraan or PPKn) at the Madrasah Ibtidaiyah (MI) level, which remains dominated by conventional and less contextual teaching methods. The research aims to examine the effectiveness of the Project Based Learning (PjBL) model in fostering students’ civic attitudes through PPKn instruction. Employing a qualitative approach with a case study design, this study was conducted at an MI in Kendari City. The informants consisted of PPKn teachers and upper-grade students. Data were collected through participant observation, in-depth interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing, with validity ensured through source and technique triangulation.The results reveal that the implementation of PjBL significantly enhances students’ sense of responsibility, cooperation, tolerance, and social awareness. These findings contribute to the theory of experiential civic education and offer practical implications for developing more transformative, contextual, and student-centered PPKn learning in primary Islamic schools.